Sistem Pengambilan Keputusan Penerimaan Beasiswa KIP Menggunakan Algoritma Fuzzy Mamdani - Ilham Arifin; RG. Guntur Alam (TIN: Terapan Informatika Nusantara, 2026)
The selection process for KIP Scholarship recipients at UINFAS Bengkulu is still conducted using conventional procedures, resulting in a relatively time-consuming process and potential subjectivity in decision-making. This study aims to develop a web-based Decision Support System using the Fuzzy Mamdani method to assist in selecting scholarship recipients in a more objective and systematic manner. The system was developed using the Waterfall model, which consists of requirements analysis, system design, implementation, testing, and maintenance. Eligibility assessment was based on four criteria: parents' income, number of family dependents, cumulative grade point average (GPA), and academic achievement, which were processed through fuzzification, IF–THEN rule-based inference, and centroid defuzzification. The main contribution of this study lies in the integration of the Fuzzy Mamdani computational model, which specifically combines financial criteria and student academic information to reduce ambiguity in scholarship selection parameters. The implementation results showed that the system produced a defuzzification value of 80 for the test data, indicating that the applicant was categorized as Eligible for the KIP Scholarship. Functional testing using the black-box testing method on seven test scenarios achieved a 100% success rate, indicating that all system functions operated as expected. The results demonstrate that the proposed system is capable of supporting the KIP Scholarship selection process in a more objective, transparent, efficient, and systematic manner compared with the previous manual process.